Tocilizumab in COVID-19: The Cerrahpaşa-PREDICT score. Issue 9 (September 2021) - Eşkazan, Ahmet Emre; Balkan, İlker İnanç; Demirbaş, Kaan Can; Ar, Muhlis Cem; Karaali, Rıdvan; Sekibağ, Yonca; Mulamahmutoğlu, Sait; Yartaş Dumanlı, Güleren; Çakmak, Fatih; Özgür Yurttaş, Nurgül; Kurt, Furkan; Aladağ Kurt, Seda; et al.
Abstract: Background: Cytokine release syndrome (CRS), characterized by overproduction of proinflammatory cytokines in the course of severe coronavirus disease 2019 (COVID-19), has been suggested as the major cause of mortality. Tocilizumab, a recombinant humanized monoclonal antibody against human IL-6 receptor, poses a therapeutic option for the treatment of CRS leading to severe acute respiratory syndrome in coronavirus-2 (SARS-CoV-2) infection. Methods: We performed a single-center retrospective study to reveal the outcome of COVID-19 patients on tocilizumab and proposed "the Cerrahpaşa-PREDICT score", a new clinical scoring system using clinical and laboratory parameters that would help predicting the 28-day mortality of COVID-19 patients receiving tocilizumab. Results: Eighty-seven patients (median age: 59 years) were included of whom 75.8% were male. Tocilizumab use significantly improved clinical and laboratory parameters. The 28-day mortality rate on tocilizumab was 16.1%. The Cerrahpaşa-PREDICT score, consisting of platelet counts, procalcitonin, D-dimer levels, SO2 R and the time from symptom onset to tocilizumab administration had a positive predictive value of 94.5% and negative predictive value of 92.9% for anticipating 28-day mortality. Conclusions: Severe COVID-19 should closely be monitored for the signs of hyperinflammation. We showed that administration of tocilizumab early in the course of the disease (prior to ICU admission) resulted in a favorable outcome. Close monitoring usually aids identifying patients who would benefit from tocilizumab. In this regard, the Cerrahpaşa-PREDICT score might serve as a practical tool for estimating the 28-day mortality in COVID-19 patients who received tocilizumab and would facilitate timely recognition of fatal cases to be evaluated for other therapeutic options.